Gamifying science education: How board games enhances engagement, motivate and develop social interaction, and learning - Mohd Kamal, Othman; Sim, Kah Ching (Springer Nature, 2024)
This study investigates the impact of gamified learning, specifically through computerised and paper-based board games, compared to conventional teaching methods on science education for 10-year-old students. We conducted an experimental design with 574 Malaysian Type Chinese Primary School participants, using preand post-tests, questionnaires, classroom observations, and interviews over three weeks. Students who engaged in gamified learning with computerised board games saw a significant improvement in academic performance (mean increase of 55.41%) and learning motivation compared to the conventional teaching group. Notably, the computerised board game group displayed the highest academic performance gains. Social interaction improved in all groups, with the mean score ranks (conventional teaching: 83.50, paper-based board games: 400.71, computerised board games:340.29), suggesting gamification’s potential to foster collaborative learning environments. Learning motivation also improved, with the mean score ranks (conventional teaching: 83.50, paper-based board games: 409.82, computerised board games:331.18). The theoretical framework integrates Activity Theory and Social Constructivism, providing a robust foundation for analysing behavioural, cognitive, and motivational aspects. This study extends beyond current research by offering empirical evidence of the pedagogical impact of computerised and paper-based board games on science education for 10-year-olds, highlighting the positive influence of innovative teaching methods. The findings suggest a potential transformation in traditional pedagogical approaches, aligning with the global pursuit of high-quality learning experiences.